Bacillus subtilis Inhibits Vibrio natriegens-Induced Corrosion via Biomineralization in Seawater - Guo, Zhangwei; Pan, Shuai; Liu, Tao; Zhao, Qianyu; Wang, Yanan; Guo, Na; Chang, Xueting; Liu, Tong; Dong, Yaohua; Yin, Yansheng (Frontiers in Microbiology, 2019)
The marine bacterium, Vibrio natriegens, grows quickly in a marine environment and can significantly accelerate the corrosion of steel materials. Here, we present an approach to inhibit Vibrio natriegens-induced corrosion by biomineralization. The corrosion of steel is mitigated in seawater via the formation of a biomineralization induced by Bacillus subtilis. The film is composed of extracellular polymeric substances and calcite, exhibiting stable anti-corrosion activity. The microbial diversity and medium chemistry tests demonstrated that the inhibition of V. natriegens growth by B. subtilis was essential for the formation of the biomineralized film.